2017
DOI: 10.1186/s13063-016-1712-7
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-inflammatory and immune regulatory effects of acupuncture after craniotomy: study protocol for a parallel-group randomized controlled trial

Abstract: BackgroundDespite recent advances in the medical and surgical fields, complications such as infection, pneumonia, or brain swelling may occur after a craniotomy. In some patients, perioperative antibiotic prophylaxis causes adverse effects such as itching, rash, or digestive conditions. Certain patients still develop infections severe enough to require a repeat operation despite antibiotic prophylaxis. Acupuncture has been used to treat inflammatory conditions, and many basic and clinical studies have provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Growing evidence has indicated that acupuncture effectively improves various inflammatory diseases through immune regulation and anti-inflammatory effects 12,13) . Pharmacopuncture is a new acupuncture treatment method in Traditional Korean Medicine (TKM).…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…Growing evidence has indicated that acupuncture effectively improves various inflammatory diseases through immune regulation and anti-inflammatory effects 12,13) . Pharmacopuncture is a new acupuncture treatment method in Traditional Korean Medicine (TKM).…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…In the original publication [ 1 ] was one author affiliation of the author Seung-Bo Yang incorrect. Only affiliation 2 belongs to Seung-Bo Yang.…”
Section: Correctionmentioning
confidence: 99%
“…Evidence suggests that acupuncture can regulate the immune system [10,11]. In humans, electroacupuncture (EAP), an application of electrical current on acupuncture needles, is reported to be effective in enhancing immune function by alleviating immunosuppression of patients during [4] and after surgery [4,11].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that acupuncture can regulate the immune system [10,11]. In humans, electroacupuncture (EAP), an application of electrical current on acupuncture needles, is reported to be effective in enhancing immune function by alleviating immunosuppression of patients during [4] and after surgery [4,11]. Similarly, in laboratory species, EAP resulted in a decrease in lymphocyte apoptosis induced by surgical trauma [12] and in a restoration of suppressed lymphocyte proliferation [4,13].…”
Section: Introductionmentioning
confidence: 99%